MODIFICATION OF LAYING DUCK FEED WITH HERBAL FEED ADDITIVES TO THE QUALITY OF LOCAL DUCK EGGS - Putra, Andhika; Wijaya Negara, Adhona Bhajana; Siswoyo, Purwo (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Increased production of duck eggs with the support of local potential in the form of feed additives is still rarely used by laying duck breeders as feed additives, in Indonesia and especially in North Sumatra, it has the potential to support herbal feed additives that are easily obtained at low prices and can even be obtained for free. Among them are turmeric, meniran and garlic which contain herbal ingredients as natural antibiotic growth promoters (AGP). The purpose of this study was to determine the benefits of adding herbal feed additives to the production and quality of local duck eggs. The research method used was a non-factorial completely randomized design method consisting of 4 treatments with 5 replications, where treatment 1 was a control ration without the addition of feed additives, treatment 2 was a control ration with the addition of 3% Garlic flour, Treatment 3 was a control ration with the addition of 3% flour and treatment 4 is the control ration with the addition of 3% turmeric flour. Observations of the research carried out were the level of feed consumption, egg production, egg weight, feed conversion and egg yolk index. The results obtained showed that the results were not significantly different in the observations of feed consumption, egg production, egg weight, feed conversion and egg yolk index. The conclusion of this study was that the addition of herbal feed additives in the ration of laying ducks did not have a significant impact on all observations, however, the data improved the quality of feed conversion and increased egg production and weight due to the performance of the essential oil content which acts as an antibiotic, prebiotic and natural phytobiotic. which is owned by turmeric, garlic and meniran. The advice given is that farmers use herbal feed additives in livestock rations to increase feed effectiveness and egg quality.